Will your workers sue you? State-by-State risks and strategic responses - Posthuma, Richard A. (Business horizons, 2012)
Every day, managers face the risk of lawsuits being filed by their workers. Lawsuits are disruptive, time consuming, expensive, and often completely unexpected/unanticipated. To better prepare for this undesirable occurrence, managers must understand the risks involved. Three metrics—frequency, severity, and range—elucidate the risks of employment lawsuits and illustrate how these may vary from one state to the next. Risk management tactics can be deployed strategically to handle the variety of risk present in various locations. These tactics create a defense-in-depth strategy with layered multiple-hurdles to stymie employee depletion of corporate assets. Rather than live in perpetual fear, employers can more successfully manage the risks of worker lawsuits.